Russian čut’: puzzles of grammaticalization - Плунгян, В. А.; Рахилина, Е. В.; Орехова, М. И. (Vilnius University Open Series, 2021)
The paper analyzes some non-trivial properties of the Russian particle čut’ (≈ ‘a little’) as well as its reduplicated counterpart čut’-čut’ used as a discourse marker. The rapid grammaticalization of čut’ started around the 17th century resulted in the coexistence of three types of values: quantitative (‘small quantity’), avertive (followed by negation and often by bylo), and immediate (‘as soon as’). This is a peculiar polysemy; what makes it even more peculiar is the fact that a large part of quantitative values related to nominal quantity is a very recent development and not an early inheritance as one might a priori expect.